Penyuluhan Resiko Hipertensi Sebagai Upaya Untuk Peningkatan Kesadaran Masyarakat Terhadap Pola Hidup Sehat - Nyoman Hepi Nusari; Dita Amelia; Teni Nopitasari; Muhammad Aditya; Suci Ramadani; Putri Meylani; Rika Wulandari; Ulia Ulia; Neri Mei Wanda; Muhammad Risky Gilang A (JURNAL PENGABDIAN KADER BANGSA, 2026)
Hypertension is a non-communicable disease and can affect anyone, this disease is called a silent killer because this disease rarely causes symptoms, in 2025 it is estimated that this disease can reach 1.56 billion where Hypertension in Indonesia in 2018 has reached 34.1%. This counseling activity aims to educate the public so that they can better understand the risks, causes, treatment and prevention of hypertension so that the public can better understand and be aware of this disease, this activity was carried out at the Polindes Purun Village, Penukal District, PALI Regency. This activity was attended by around 35 participants with blood pressure checks at the beginning of the event and a short pretest and posttest were carried out to measure the level of participants' understanding of hypertension. From the data obtained, 88.6% of participants had blood pressure above 120/80 mmHg, with pretest results of 40% of participants having poor knowledge about hypertension, and after counseling, participants who had poor knowledge decreased to 11.4%, this shows an increase in participants' ability regarding hypertension. This activity is expected to be an educational chain so that it is hoped that it can reduce the number of cases of hypertension.